2005
DOI: 10.1038/sj.bjp.0706205
|View full text |Cite
|
Sign up to set email alerts
|

Artocarpol A stimulation of superoxide anion generation in neutrophils involved the activation of PLC, PKC and p38 mitogen‐activated PK signaling pathways

Abstract: 1 Artocarpol A (ART), a natural phenolic compound isolated from Artocarpus rigida, stimulated a slow onset and long-lasting superoxide anion generation in rat neutrophils, whereas only slightly activated the NADPH oxidase in a cell-free system. 2 Pretreatment of neutrophils with pertussis toxin (1 mg ml À1 ), 50 mM 2 0 -amino-3 0 -methoxyflavone (PD 98059), or 1 mM 1,4-diamino-2,3-dicyano-1,4-bis(2-aminophenylthio)butadiene (U0126) had no effect on ART-stimulated superoxide anion generation. ART (30 mM) did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Data summarized in Fig. 1B Several studies showed that stimulation of PKC enhanced the activity of MAPK such as P38 and ERK (5,14,25) which have been shown to inhibit the SK channels (3). Thus we examined the role of P38 and ERK in mediating the effect of PGE 2 on the SK channels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data summarized in Fig. 1B Several studies showed that stimulation of PKC enhanced the activity of MAPK such as P38 and ERK (5,14,25) which have been shown to inhibit the SK channels (3). Thus we examined the role of P38 and ERK in mediating the effect of PGE 2 on the SK channels.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of K intake on ERK and P38 MAPK phosphorylation is at least partially mediated by superoxide and related products because suppressing superoxide levels with tempol abolished the effect of low-K intake on P38 and ERK phosphorylation (3). It is also well-established that stimulation of PKC could activate MAPK in a variety of cells (5,14,25). Although the mechanism by which PKC activates MAPK is not completely understood, PKC could activate NADPH oxidase by phosphorylation of p47phox (6) and increase the superoxide generation that stimulates the phosphorylation of ERK and P38 MAPK (3).…”
Section: Discussionmentioning
confidence: 95%
“…By contrast, apigenin and kaempferol induce apoptosis in tumor cells through activation of their mitochondrial NADPH-oxidase and intracellular oxidative stress [106]. The plant polyphenol artocarpol A up-regulates NADPH-oxidase in neutrophils by stimulating of PKC activation through p38 mitogen-activated protein kinase phosphorylation [107].…”
Section: Interaction With Oxidant-producing and Antioxidant Enzymesmentioning
confidence: 98%
“…Conventional PKC (cPKC), which is synergistically activated by DG and Ca 2ϩ in conjunction with phosphatidylserine (PS) (12,13), has been suggested to play a role in superoxide generation and degranulation (14,15). In addition, PI3K and MAPK are also suggested to be involved in these neutrophil events (16)(17)(18)(19)(20). Thus, the molecular mechanisms which regulate superoxide generation and degranulation are very complicated.…”
mentioning
confidence: 99%